1967
DOI: 10.2466/pr0.1967.21.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Einstellung by Observation

Abstract: In 2 experiments female Ss observed a confederate solve G "water-jar" problems. Each problem permitted 2 modes of solution. In Exp. I the 3 conditions were observation of direct solutions, indirect solutions, or a mixture of both. In subsequent performances on similar problems, observers adopted the solution methods that had been observed even when inefficient. In Exp. I1 the order of the jar capaciti~s was varied to test for the acquisition by observation of a more general solution set. The 3 conditions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1973
1973
1979
1979

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…The theories of Piaget and Inhelder (1969) and Liebert and Swenson (197la, 1971b) imply that imitation involves abstraction. Both are consistent with the findings that observers do abstract and generalize information received from a model (Bandura & Harris, 1966;Debus, 1970;Denny, 1972;Laughlin, Moss, & Miller, 1969;Liebelt & Swenson, 197la, 1971b;Rosenbaum & Aronson, 1967;Rosenthal & Zimmerman, 1972;Rosenthal, Zimmerman, & Durning, 1970;Waghorn & Sullivan, 1970). However, Piaget and Inhelder also imply that an observer's ability to represent symbolically, abstract, and generalize from observation of a model depends on the stage of the observer's cognitive operations (age) and the logical structure of the task modeled.…”
supporting
confidence: 65%
“…The theories of Piaget and Inhelder (1969) and Liebert and Swenson (197la, 1971b) imply that imitation involves abstraction. Both are consistent with the findings that observers do abstract and generalize information received from a model (Bandura & Harris, 1966;Debus, 1970;Denny, 1972;Laughlin, Moss, & Miller, 1969;Liebelt & Swenson, 197la, 1971b;Rosenbaum & Aronson, 1967;Rosenthal & Zimmerman, 1972;Rosenthal, Zimmerman, & Durning, 1970;Waghorn & Sullivan, 1970). However, Piaget and Inhelder also imply that an observer's ability to represent symbolically, abstract, and generalize from observation of a model depends on the stage of the observer's cognitive operations (age) and the logical structure of the task modeled.…”
supporting
confidence: 65%
“…In some studies, observers were superior to performers in correct responding at test trials (Hillix and Marx, 1960; Rosenbaum and Arenson, 1968;Eelen and d'Ydewalle, 1976), whereas the opposite was true in the study of Van Wagener and Travers (1963) and no differences were reported by Cheyne (1972) and Marx and Witter (1972). It seems fair to conclude that there is no general answer to the question which training procedure is most efficient.…”
Section: Introductionmentioning
confidence: 83%
“…More recently, learning within this classical procedure was compared to learning by subjects who were not required to respond overtly during the study trial (Hillix and Marx, 1960; Rosenbaum and Arenson, 1968;Marx and Witter, 1972; Eelen and d'Ydewalle, 1976). These subjects received equivalent information about responses and outcomes either by observing another subject perform the task or by receiving appropriate instructions from the experimenter.…”
Section: Introductionmentioning
confidence: 98%